STUDI LITERATUR HUBUNGAN HIPERTENSI DENGAN KETAJAMAN PENGLIHATAN PADA PENDERITA DIABETES MELLITUS TIPE 2 - Rahman Man Nasar (Jurusan Keperawatan Poltekkes Kemenkes Makassar, 2021)
ABSTRACT Decreased visual acuity is a disorder in the eye that affects vision causing blurred vision. Decreased visual acuity can occur in most DM patients, this is a big threat for people with Diabetes Mellitus because it can cause diabetic retinopathy and even blindness. The purpose of this literature study is structured to present the relationship of hypertension with visual acuity in patients with Type 2 diabetes mellitus.This literature search is carried out to obtain articles that fit the topic through the Google Scholar database by using keywords or Hypertension search with visual acuity in diabetes